Chronic cholecystitis with Cystoisospora belli in an immunocompetent patient. (11th June 2015) - Takahashi, Hideo; Falk, Gavin A; Cruise, Michael; Morris-Stiff, Gareth
Abstract : A 47-year-old woman presented with a history of vague abdominal pain for several years, which worsened over the past 2 months, with pain more prominent in the right upper quadrant. She also had a history of peptic ulcer disease. The ultrasound scan of right upper quadrant revealed normal gallbladder and oesophagogastroduodenoscopy was unremarkable. A 99m technetium labelled hepato iminodiacetic acid (HIDA) scan with cholecystokinin provocation demonstrated a decreased gallbladder ejection fraction (EF) of 32%. On this basis, the patient was diagnosed with biliary dyskinesia and underwent an elective laparoscopic cholecystectomy. Histopathological analysis revealed chronic cholecystitis with Cystoisospora belli identified in the gallbladder wall. Cystoisospora has been identified to cause an opportunistic acalculous cholecystitis among immunocompromised hosts, especially those with AIDS. This is the first case report of chronic cholecystitis due to C. belli in an immunocompetent patient.